2021
DOI: 10.3389/fcimb.2021.579766
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth Is Correlated With Increased Oral Originated Microbiome in the Gut

Abstract: BackgroundPreterm birth is one of the leading causes of perinatal morbidity and mortality. Gut microbiome dysbiosis is closely related to adverse pregnancy outcomes. However, the role of the gut microbiome in the pathogenesis of preterm birth remains poorly studied.MethodWe collected fecal samples from 41 women (cases presenting with threatened preterm labor =19, 11 of which delivered preterm; gestational age-matched no-labor controls, all of which delivered at term = 22) were recruited for the study. We perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 41 publications
1
22
0
1
Order By: Relevance
“…Another case-control study showed that pregnant women with pre-eclampsia (PE) had a high abundance of Fusobacterium and Veillonella and a relatively low abundance of Faecalibacterium and Akkermansia compared with normotensive pregnant women (Chen C. et al, 2020;Chen X. et al, 2020). Yin et al (2021) reported that women with preterm birth (PTB) showed a distinct gut microbiome dysbiosis compared with those who delivered at term. Opportunistic pathogens, particularly Porphyromonas, Streptococcus, Fusobacterium, and Veillonella, were enriched, while Coprococcus and Gemmiger were markedly depleted in the preterm group (Yin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another case-control study showed that pregnant women with pre-eclampsia (PE) had a high abundance of Fusobacterium and Veillonella and a relatively low abundance of Faecalibacterium and Akkermansia compared with normotensive pregnant women (Chen C. et al, 2020;Chen X. et al, 2020). Yin et al (2021) reported that women with preterm birth (PTB) showed a distinct gut microbiome dysbiosis compared with those who delivered at term. Opportunistic pathogens, particularly Porphyromonas, Streptococcus, Fusobacterium, and Veillonella, were enriched, while Coprococcus and Gemmiger were markedly depleted in the preterm group (Yin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al (2021) reported that women with preterm birth (PTB) showed a distinct gut microbiome dysbiosis compared with those who delivered at term. Opportunistic pathogens, particularly Porphyromonas, Streptococcus, Fusobacterium, and Veillonella, were enriched, while Coprococcus and Gemmiger were markedly depleted in the preterm group (Yin et al, 2021). However, whether these associations are causal has not been established because of potential biases including residual confounding factors and reverse causality.…”
Section: Introductionmentioning
confidence: 99%
“…The general uptrend of Veillonella spp. abundance was shown in several studies in healthy and preterm infants ( Dzidic et al, 2018 ; Yin et al, 2021 ; Xu et al, 2022 ). In this study, the relative abundance of V. dispar also increased while growing up in both groups; however, V. atypica did not show this trend, which was stable in the healthy controls from CT0 to CT1 stage and decreased markedly in the preterm infants along with two lower primary central incisors teeth eruption.…”
Section: Discussionmentioning
confidence: 77%
“…138,139 The previous microbiome reported in placenta seemed to be of more possibility of contamination from sampling or procedure of sample processing. 140,141 Besides the microbiome in genital tract, a decrease in a-diversity of microbiome, 142 and increased oral originated bacteria 92 in the gut were both correlated with sPTL.…”
Section: Interactions Between External and Internal Factorsmentioning
confidence: 99%